Swami Vivekananda : The Icon before the Indian Youth: Reviving the Need for Inspirational Icons (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The modern mind frowns upon hero worship. Worshipping an ideal man, historical or mythical, is perceived as a psychological weakness that has to be outgrown sooner than later. The trainer asked the participants whether they had a personal idol and then went on to explain that no man is perfect and that looking up to a role model for perfection is a naive beliefThis attitude of cynicism towards ideals is undoubtedly at the root of the degeneration of personal values we see all around us today. I don’t think it is necessary to mention the depressing long list of problems plaguing humanity in general today and in Indian society in particular, to convince ourselves that we are in the midst of a crisis of values and leadership.The Indian youth are restless for change today. They have had too much of theoretical philosophising and hair splitting discussions. They are thirsting for leadership, for a man of action who can bring the change they much desire. They are fed up of the ubiquitous hypocrites who talk too much and do too little. They are thirsting for an icon, a leader who can walk the talk and reverse this steep fall.